CARBAPENEM-RESISTANT ACINETOBACTER BAUMANNII: THE ROLE OF SELECTED MICROBIOLOGICAL AND BIOCHEMICAL FACTORS IN TARGETED THERAPY SELECTION — A NARRATIVE REVIEW - Lamorski, Jakub; Szubert, Izabela; Suchecka, Julia; Nesterak, Wiktor; Chudecka, Karolina; Chylewski, Michał; Kędzierska, Aleksandra; Józwa, Katarzyna; Stępień, Gabriela; Przewoźna, Urszula (International Journal of Innovative Technologies in Social Science, 2026)
Carbapenem-resistant Acinetobacter baumannii (CRAB) strains represent one of the major challenges in contemporary medicine because of features that contribute to both the high mortality rate of infections and the ease of their dissemination within the hospital environment. The aim of this study was to analyze resistance mechanisms, including the biochemical basis of selected mechanisms and their impact on the selection of targeted therapy. This review discusses the key mechanisms underlying carbapenem resistance, including enzymatic mechanisms associated with β-lactamase production, as well as non-enzymatic mechanisms involving efflux pump overexpression, alterations in membrane permeability, modification of target sites, and biofilm formation. The analysis also included the genetic background of the major resistance mechanisms. Particular attention was devoted to class B and D enzymes due to their high prevalence and broad substrate activity spectrum, which contributes to the ineffectiveness of numerous antibiotic groups. The characteristics of individual antibiotics were discussed in the context of their impact on therapeutic efficacy in infections caused by CRAB strains, together with selected novel therapeutic options, both currently used and still under investigation. The growing importance of molecular diagnostic methods, including whole-genome sequencing, as well as bioinformatics tools used both for the improvement of diagnostic methods and for monitoring the epidemiological situation at both local and global levels, was also emphasized. One of the principal conclusions of this study is the necessity for further high-quality clinical research aimed at generating more robust clinical data to support the development of effective treatment regimens.